Act1, an NF-κ B-activating Protein - Li, Xiaoxia; Commane, Mairead; Nie, Huiqin; Hua, Xianxin; Chatterjee-Kishore, Moitreyee; Wald, David; Haag, Michael; Stark, George R. (Proceedings of the National Academy of Sciences - PNAS, 2000)
Use of an NF-κ B-dependent selectable marker facilitated the isolation of a cell line containing a cDNA encoding Act1, an NF-κ B activator. Act1 associates with and activates Iκ B kinase (IKK), leading to the liberation of NF-κ B from its complex with NF-κ B. Many signaling pathways that liberate NF-κ B also activate activating transcription factor (ATF) and activator protein 1 (AP-1) through Jun kinase (JNK). Act1 also activates JNK, suggesting that it might be part of a multifunctional complex involved in the activation of both NF-κ B and JNK. Act1 fails to activate NF-κ B in an IL-1-unresponsive mutant cell line in which all known signaling components are present, suggesting that it interacts with an unknown component in IL-1 signaling.